Distributive Justice of the Participation of the Interested Assets According to the Civil and Khi Kuh in the Maqashid Al-Sharia'ah Perspective - Purnomo; Ahmad Hasan Ridwan (Journal of Islamicate Studies, 2021)
Inheritance is a division of property in the family to do when someone has died. Civil Code and KHI have the same three elements, namely the heir, heirs, and something that can be taken advantage for granted. Civil Code establishes the rules of inheritance in two ways, namely by Law (ab-intestato) and with a will (testament). KHI set rules about their automatically down to children or derivatives or family as already set out in the Koran. Specifications of this research is descriptive, with a normative juridical approach. Research supported by the method of approach to legislation (Statute Approach) nationwide, and the approach of the case (Case Approach), philosophy of law, legal history, the study was supported by the methods of interpretation of law (systematic and authentic), and comparative law.